2018
DOI: 10.1371/journal.pone.0207526
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulation of the follicle-stimulating hormone receptor. Understanding the conformational dynamics of receptor variants at positions N680 and D408 from in silico analysis

Abstract: Follicle-stimulating hormone receptor (FSHR) is a G-protein coupled receptor (GPCR) and a prototype of the glycoprotein hormone receptors subfamily of GPCRs. Structural data of the FSHR ectodomain in complex with follicle-stimulating hormone suggests a “pull and lift” activation mechanism that triggers a conformational change on the seven α-helix transmembrane domain (TMD). To analyze the conformational changes of the FSHR TMD resulting from sequence variants associated with reproductive impairment in humans, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 63 publications
0
22
0
Order By: Relevance
“…Initial box dimensions were 90 Å x 105 Å x 114 Å, respectively, for the x-, y- and z-axis. A total of 128979 atoms were included: 29231 water molecules, 248 SDPC lipid molecules, a sodium ion for charge neutrality, and the receptor FSHR-WT or mutant I423T, with 379 residues encompassing D317 to N695 [28].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Initial box dimensions were 90 Å x 105 Å x 114 Å, respectively, for the x-, y- and z-axis. A total of 128979 atoms were included: 29231 water molecules, 248 SDPC lipid molecules, a sodium ion for charge neutrality, and the receptor FSHR-WT or mutant I423T, with 379 residues encompassing D317 to N695 [28].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, we implemented a computational approach to determine the impact of point mutations in the interhelical region of the FSHR [28]. Interestingly, the conformational dynamics of the wild-type receptor (FSHR-WT), was sensitive to point mutations such as D408Y and D408A, according to an analysis of autocorrelation matrices of the helical domains [28]. Apparently, when replacing D408 by tyrosine or alanine, fluctuations in protein backbone atoms showed different patterns in correlated communities in a dynamical network analysis [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently employed computational modeling and molecular dynamics simulations (MDS) of the FSHR in an explicit membrane environment [pre-equilibrated lipid bilayer of 1-stearoyl-2-docosahexaenoyl-sn-glycero-3-phosphocholine (SDPC) molecules] as a tool to explore in more detail the impact of the substitution of aspartate with tyrosine, alanine, or arginine at position 408 [122]. The FSHR modelled allowed us to detect differences in the receptor dynamics at the transmembrane domains between the WT and mutant receptors, likely related to receptor function.…”
Section: Misfolded Gonadotropin Receptors As a Cause Of Hypergonadotropic Hypergonadismmentioning
confidence: 99%
“…In these three-dimensional representations, it can be observed that the dynamics of the receptor disclosed differences in the amplitudes of interhelical domains (arrows) as a function of the mutation at position 408. See the text and Refs [115,122]. for data and details.…”
mentioning
confidence: 99%